Prenatal sonographic findings and management of placental mesenchymal dysplasia - Suchaya Luewan; Pakorn Chaksuwat; Tip Pongsuvareeyakul; Theera Tongsong (Clinical and Experimental Obstetrics & Gynecology)
Placental mesenchymal dysplasia (PMD) is a rare disorder of the placenta characterized by placentomegaly with diffuse hydropic stem villous, aneurysmally dilated vessels, and lack of trophoblastic proliferation. Case: The prenatal ultrasound of a 34-year-old woman (G1P0) at 33 weeks of gestation showed an enlarged placenta with multiple cystic lesions, heterogeneous echoes with no active blood flow, and fetal growth restriction (FGR). The differential diagnosis involved partial mole, placental hemorrhage, and PMD. She developed preeclampsia at 38 weeks of gestation and gave birth to a normally formed, growth-restricted baby. The placenta, weighing 785 g, showed scattered cystic vesicles in the parenchyma. The histology shows enlarged edematous stem villi with occasional cistern formation and no area of chorioangioma or features of molar pregnancy. PMD associated fetal growth restriction was diagnosed. Conclusion: PMD has prenatal ultrasound result resembling those of partial mole, placental hemorrhage and chorioangioma, but the fetus is phenotypically normal. Nevertheless, fetal surveillance is essential.